2013
DOI: 10.1021/ma302666e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating Rate on the Pathway for Vesicle Formation in Salt-Free Aqueous Solutions of Thermosensitive Cationic Diblock Copolymers

Abstract: Amphiphilic diblock copolymers composed of a thermo-responsive poly(2-isopropyl-2-oxazoline) (PIPOZ) block (M n = 7000 g/mol) linked to a poly(3acrylamidopropyl)trimethylammonium chloride) (PAMPT-MA) block (M n = 3500 or 8200 g/mol) were prepared by cationic ring-opening polymerization (PIPOZ block) and subsequent atom transfer radical polymerization (PAMPTMA block). Salt-free dilute aqueous solutions of the diblock copolymers underwent a reversible phase transition upon heating past 40 °C that led to the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 49 publications
4
51
0
Order By: Relevance
“…Note that addition of further D2O to the D2O NMR sample led to no change in the spectra. Similar phenomena have been observed for thermosensitive block-copolymers, 28 where proton signals disappeared upon thermal stimulation and subsequent coiling of the polymer. Interestingly however, such behaviour has not been reported for other POM-surfactant systems to date.…”
supporting
confidence: 80%
“…Note that addition of further D2O to the D2O NMR sample led to no change in the spectra. Similar phenomena have been observed for thermosensitive block-copolymers, 28 where proton signals disappeared upon thermal stimulation and subsequent coiling of the polymer. Interestingly however, such behaviour has not been reported for other POM-surfactant systems to date.…”
supporting
confidence: 80%
“…This water content is due to both water trapped within the layer and water directly hydrating the polymer chain, and we note that Korchagina et al reported that the PIPOZ chains of the diblock copolymer were not fully dehydrated even above the phase-transition temperature. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Poly(2-isopropyl-2-oxazoline) 60 -b-poly((3-acrylamidopropyl)trimethylammonium) 17 , abbreviated as (PIPOZ 60 -b-PAMPTMA 17 ), was prepared as described previously with a molecular weight M n of 10.3 kDa (Figure 1). 22 The nonionic block, PIPOZ, has a M n of 7.0 kDa with M w /M n = 1.06 as determined by GPC, 31 corresponding to ∼60 repeat units. This polymer was used here in control experiments aimed at evaluating the adsorption of PIPOZ on silica surfaces.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations